Strategies for Village Economic Empowerment and Optimization of Village-Owned Enterprises (BUMG) in the Digital Era: Evidence from Gampong Panyang and Tangkeh, Woyla Timur District, West Aceh - Mutiara Shifa; Muhammad Rahmat Hidayat; Sri Rosmiati Sani; Puput Arisna; T. Jalaluddin (Outline Publisher, 2026)
This community service program aims to strengthen the role of Village-Owned Enterprises (BUMG) in supporting local economic development through digital-based empowerment strategies. Conducted in Gampong Panyang and Tangkeh, Woyla Timur District, West Aceh, the program addressed key challenges such as limited managerial capacity, low digital literacy, and restricted market access. A participatory approach was applied, including needs assessment, socialization, training, mentoring, and evaluation. The results show significant improvements in participants’ knowledge and skills, especially in digital marketing, financial management, and the use of simple digital tools for business operations. Additionally, there was a positive shift in community attitudes toward technology adoption, reflected in increased participation in digital-based economic activities. The program also strengthened the institutional capacity of BUMG through improved management practices, enhanced financial transparency, and better business planning. Although challenges such as limited digital infrastructure and varying levels of technological readiness persist, the findings demonstrate that integrating capacity building with digital transformation can improve the performance of rural enterprises. Overall, digital-based community empowerment is an effective strategy to enhance the sustainability and competitiveness of village economies and has strong potential for replication in similar.